Nanocrystalline-to-amorphous Transformation of Silicon Carbide Induced by Atomic Displacement Events. Issue 1 (1st January 2023) - Chen, Dong; Guo, Zhiheng; Zheng, Danting; Tian, Zihan; Shi, Qingyang; Mao, Yandong
Abstract: In nanocrystalline silicon carbide (NC-SiC), nanocrystalline-to-amorphous (NC-A) transformation can be induced due to atomic displacement events. To evaluate the detailed mechanisms of radiation resistance to amorphization and understand the role of grain boundaries (GBs), it is significantly critical to determine the amorphized dose of NC-SiC by inducing atomic displacements and obtain the information of defect behaviors in the NC-A transformation by using molecular dynamics methods. The results of this study revealed that full amorphization of NC-SiC was achieved by randomly displace (1) a Si atom or (2) a Si/C atom at the same dose of displacement per atom (dpa). The migration of carbon interstitial is the driving force in the amorphization process of NC-SiC according to the low migration energy of carbon in 3C-SiC. Moreover, defect clusters subsequently form and merge into the amorphous domains at the GBs, which will reveal the microscopic mechanism of the irradiation-induced NC-SiC amorphization.